Analysis of flexible antenna performance on partial discharges detection. (January 2020) - Affendi, N A M; Amirruddin, M; Ahmad, S
Abstract: This paper reports a short finding on the use of a flexible substrate in the design of Partial discharge (PD) detection antenna. This flexible antenna was designed and simulated using CST Microwave Studio to detect corona discharge which is one types of PD that occur in power transformers. The flexible substrate that been used in designing the antenna is paper that has permittivity of 3.2 and the chosen frequency is between 300MHz until 3GHz. The overall dimension is 208×168×1.6 mm3. The simulations of the antenna's return loss were conducted under two conditions; 1) flat and 2) bending along H- planes. The result were been analysed to understand the performance of paper properties, so that practical system requirements are met. This implies that the performance of paper antennas can be used in the PD field with altering some of the characteristic to upgrade its performance.